Peutz-Jeghers syndrome: an unusual autopsy finding in pregnancy - Michell Frank Alves de Oliveira; Maria Aparecida Marchesan Rodrigues (University of São Paulo, 2021)
Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant polyposis entity that often remains undiagnosed. The major problems associated with PJS are acute complications due to (i) polyp-related intestinal obstruction, (ii) intussusception, and (iii) the risk of cancer in the long-term. We report the case of a 32-year-old female who presented at the emergency room with signs of acute abdomen and died during the clinical workup. She had a one-month history of nausea, vomiting, and diarrhea and was pregnant at about 30 weeks. There was no contributing past history except for undergoing small bowel resection in infancy. The postmortem examination revealed multiple arborizing polyps throughout the gastrointestinal tract, chiefly in the small bowel. Intestinal obstruction was found at the proximal jejunum with necrosis, perforation, and peritonitis. Histologically, the polyps were composed of tree branch-like bundles of smooth muscle covered by normalappearing glandular epithelium, confirming the diagnosis of hamartomatous polyps. No malignant or premalignant lesions were detected in the gastrointestinal tract or other organs. This case was an opportunity to analyze the natural history and the pathological features of the Peutz-Jeghers syndrome in an adult and to investigate the presence of neoplastic lesions associated with this condition.